2016
DOI: 10.1177/0333102416648656
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and repeatability of testing visual evoked potential habituation in migraine: A blinded case–control study

Abstract: Background: Many studies have shown that migraine patients have an interictal habituation deficit of visual evoked potentials (VEPs). Some discordant results were attributed to non-blinded analyses and a lack of repeatability. Aims: In this study, we compared blinded and non-blinded analyses of the same recordings and assessed test-retest repeatability. Methods: VEP recordings of 25 healthy volunteers (HVs) and 78 episodic migraine patients (EMs; 52 interictal, 26 ictal) were analysed by two investigators, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…The habituation response was calculated according to the 10th‐1st block response, which is compatible with 1000 VEP responses per eye. In some studies, the variability of pattern reversal visual evoked responses has been attributed to the presence of the blinding method . In our study, all cursors of N1‐P1 peak marks were marked offline by an experienced neurophysiology technician, who was blinded to the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The habituation response was calculated according to the 10th‐1st block response, which is compatible with 1000 VEP responses per eye. In some studies, the variability of pattern reversal visual evoked responses has been attributed to the presence of the blinding method . In our study, all cursors of N1‐P1 peak marks were marked offline by an experienced neurophysiology technician, who was blinded to the groups.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the variability of pattern reversal visual evoked responses has been attributed to the presence of the blinding method. 19 In our study, all cursors of N1-P1 peak marks were marked offline by an experienced neurophysiology technician, who was blinded to the groups. Some genetic differences in sensory processing between individuals and effects of sexual hormones may also change cortical excitability in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we acknowledge as a limitation of the present study the lack of inclusion of a patients control group staying on the waiting-list not undergoing the dietetic intervention in order to control for effects of repeated measurements at the neurophysiological level and for unpredictable spontaneous clinical improvement. However, this point should not consider to be detrimental since a recent study in migraine proved that, at least for the visual modality, evoked potential amplitude habituation has a sufficient repeatability over an average test-retest time interval of 60 days [ 49 ], and because we previously proved that only 1-month KD, but not a standard diet, was clinically effective in a population of migraine patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the blinding problem, it is worth mentioning that one IDAP study (17) and four VEP studies (35)(36)(37)(38) that confirmed the electrophysiological abnormalities in migraine were blinded for the analyses. In a very recent study (39), the same VEP data were analysed separately by two investigators, one of them blinded to the migraine diagnosis and phase. The analyses by both confirmed interictal VEP habituation deficit in episodic migraine and normal VEP habituation in healthy volunteers and migraine patients during an attack.…”
Section: Discussionmentioning
confidence: 99%